Cosmetic Products and Industry (IntechOpen, 2024)
In Cosmetic Products and Industry - New Advances and Applications, we embark on a journey through the heart of cosmetic science, guided by the expertise of global luminaries in the field. This edited book is a collection of scholarly articles that traverse the scientific landscape of cosmetic innovation. From unraveling the mysteries of cosmetic ingredients to unveiling the fundamental technologies and research that breathe life into cosmetics, and from conjuring innovative concepts applied to formulations to ensure the safety of every ingredient, this volume includes contributions that push the boundaries of knowledge in cosmetic science.